Huaier suppresses lung cancer by simultaneously and independently inhibiting the antioxidant pathway SLC7A11/GPX4 while enhancing ferritinophagy - Xingxing Shi; Kun Liu; Yuchang Tian; Xinyi Bi; Junkai Zhang; Fengyi Ma; Wensheng Wei; Tongbiao Zhao (Cell Death Discovery)
Abstract Huaier (Trametes Robiniophila Murr), a traditional Chinese medicine, has emerged as a promising therapeutic agent against cancers in clinical settings, yet its underlying mechanisms remain elusive. In this study, we demonstrate that Huaier effectively suppresses lung cancer by inducing ferroptosis. Mechanistically, Huaier simultaneously and independently downregulates the antioxidant pathway SLC7A11/GPX4 and elevates intracellular iron levels through NCOA4-mediated ferritinophagy degradation of FTH1 in lung cancer cells. Both the iron chelator deferoxamine (DFO) and the ferroptosis inhibitor ferrostatin-1 (Fer-1) mitigate Huaier-induced cell death. In both urethane-induced lung tumorigenesis models and cell-derived xenograft (CDX) models, Huaier significantly inhibits tumor progression by inducing ferroptosis, which can be counteracted by SRS16-86. Our study uncovers a novel mechanism by which Huaier induces ferroptosis to suppress lung cancer, underscoring its potential as a therapeutic agent for lung cancer or as part of a combination therapy strategy.